2021
DOI: 10.4103/ajns.ajns_406_20
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-associated acute disseminated encephalomyelitis: A systematic review

Abstract: Objective: The objective of this study was to provide an overview of acute disseminating encephalomyelitis, a potential and serious complication of COVID-19. Methods: Three primary databases were used, PubMed, LitCovid, and WHO. The final review articles reported acute disseminated encephalomyelitis (ADEM) in COVID-19-positive patients and were full-text, peer-reviewed articles. Articles which did not have patient data such as in vitro studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…Although the exact underlying mechanism of ADEM is still a matter of discussion, it is suggested that ADEM mainly occurs after bacterial and viral infection alongside vaccination [ [12] , [13] , [14] ]. Several studies have reported ADEM occurrence after SARS-CoV-2 infection [ [15] , [16] , [17] ]. Moreover, a large number of case reports and case series have also suggested the potential association between ADEM and COVID-19 vaccination [ [18] , [19] , [20] , [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact underlying mechanism of ADEM is still a matter of discussion, it is suggested that ADEM mainly occurs after bacterial and viral infection alongside vaccination [ [12] , [13] , [14] ]. Several studies have reported ADEM occurrence after SARS-CoV-2 infection [ [15] , [16] , [17] ]. Moreover, a large number of case reports and case series have also suggested the potential association between ADEM and COVID-19 vaccination [ [18] , [19] , [20] , [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute disseminated encephalomyelitis-like abnormalities were commonly observed in pediatric patients with severe complications, due to a SARS-CoV-2 infection [11]. This disorder causes inflammation of the brain and spinal cord, as well as damage to the white matter of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…It most commonly occurs in children but has been described in postinfectious states in adults, with much lower rates seen after vaccination. 1 , 2 , 3 Classically, the clinical presentation is an abrupt onset of mental status changes ranging from lethargy to coma, with multifocal neurologic deficits, and may include seizures. 4 Magnetic resonance imaging is paramount for proper diagnosis ( Figure 2 ) and uniformly demonstrates T2-weighted image hyperintensities, which are typically widespread, asymmetric, patchy lesions involving supratentorial and infratentorial white matter but may also involve gray matter.…”
Section: Diagnosismentioning
confidence: 99%